Equilibrium Positions for UAV Flight by Dynamic Soaring - Bingjie Zhu; Zhongxi Hou; Shangqiu Shan; Xinzhu Wang (International Journal of Aerospace Engineering)
Dynamic soaring is a special flying technique designed to allow UAVs (unmanned aerial vehicles) to extract energy from wind gradient field and enable UAVs to increase the endurance. In order to figure out the energy-extraction mechanisms in dynamic soaring, a noninertial wind relative reference frame of aircraft is built. In the noninertial frame, there is an inertial force which is created by gradient wind field. When the wind gradient (GW) and the components of airspeed (vzvx) are positive, inertial force (F) makes positive work to the aircraft. In the meantime, an equilibrium position theory of dynamic soaring is proposed. At the equilibrium positions, the increased potential energy is greater than the wasted kinetic energy when the aircraft is flying upwards. The mechanical energy is increased in this way, and the aircraft can store energy for flight. According to the extreme value theory, contour line figures of the maximum function and the component of airspeed (vz) are obtained to find out the aircraft’s lifting balance allowance in dynamic soaring. Moreover, this equilibrium position theory can also help to conduct an aircraft to acquire energy from the environment constantly.